Migrasi Muslim India ke Barus Tapanuli Tengah di Abad ke-20 M: Sebuah Tinjauan Sejarah - Irsyad, Muhammad Rifqi; Fitri, Hadiani; Sumantri, Pulung (Medan Resource Center, 2023)
This study explores the 20th-century entry of Indian-Muslim ethnic groups into Barus, Central Tapanuli, aiming to understand the historical context. It focuses on three key aspects: 1) the migration factors driving Indian-Muslims to Barus, encompassing both push and pull factors; 2) the responses of the Barus residents towards Indian-Muslim newcomers; and 3) the professions pursued by the Indian-Muslim community in Barus. Employing qualitative and library-based research methods, data was collected through interviews, observations, and documentation, subsequently verified and analyzed. The findings highlight the influence of various push factors, primarily the unfavorable social and economic conditions in their hometowns, and the pull factors include economic opportunities and the religious significance of the Barus region. The indigenous people of Barus generally welcome Indian-Muslim newcomers, fostering integration through social and economic interactions, as well as cross-cultural marriages and the granting of Batak clan names to Indian-Muslim ethnic groups. Notably, Indian-Muslims predominantly engage in professions akin to the local Barus population, such as agriculture, fishing, trading, and various services.